Acceptance of multiple micronutrient supplementations (MMS) and iron and folic acid supplement utilisation among pregnant and lactating women in the rural part of Ethiopia, 2022: a cross-sectional study - Zewdie Birhanu; Menen Tsegaw; Stanley Chitekwe; Ramadhani Noor; Rachana Sharma; Finina Abebe; Yordanos Tadesse Kidanemariam; Ahmednasir Abdi; Hiwot Getachew; Asli Hassan Aden; Tesfaye Chuko; Tariku Dejene; et al. (BMJ Open)
Objective To assess the acceptance of multiple micronutrient supplements and current iron and folic acid supplement utilisation among pregnant and lactating women in rural Ethiopia.Design Community-based cross-sectional study using a mixed method.Setting This study was carried out in five regions (Oromia, Gambela, Sidama, SNNPR (Southern Nations, Nationalities and Peoples Region) and Somali) of Ethiopia, 2022. A multistage random sampling technique was employed. A structured questionnaire was used to collect data from 410 pregnant and lactating women. A purposive sampling technique was used to select participants for the five Focused Group Discussions and fifteen Key Informant Interviews. Both bivariable and multivariable logistic regression analysis was conducted with a p value<0.05, and a 95% CI was considered statistically significant. Qualitative data were coded and analysed thematically.Participants A total of 410 pregnant and lactating women.Results The overall level of iron-folic acid utilisation was 59.3%. The odds of using iron-folic acid among pregnant and lactating women in the Sidama region are significantly lower compared with Oromia (adjusted OR (AOR)=0.12, 95% CI: 0.04, 0.38). Lactating women have significantly lower odds of using iron-folic acid compared with pregnant women (AOR=0.09, 95% CI: 0.05, 0.17). Taking medication or supplements significantly increases the odds of iron-folic acid use (AOR=2.41, 95% CI: 1.16, 4.95). Recommending a new nutrition supplement significantly increases the odds of iron-folic acid use (AOR=2.38, 95% CI: 1.21, 4.68).Conclusions The consumption of iron-folic acid supplements among pregnant and lactating women in Ethiopia is lower than in other studies. Factors associated with iron-folic acid utilisation include region, taking medication/supplements, recommending nutrition and being a lactating mother. To ensure accessibility, the product should be sold in all town shops, pharmacies and through home delivery. Additionally, a strategy should be developed to provide access to the product in each adjacent community centre. Awareness creation should be a priority for community members to avoid misconceptions about pregnancy-related supplements.